2018
DOI: 10.3389/fpls.2018.00655
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins: Their Impact on Molecular and Growth Responses to Drought Stress and Recovery in Arabidopsis

Abstract: Our phenotyping and hormonal study has characterized the role of cytokinins (CK) in the drought and recovery responses of Arabidopsis thaliana. CK down-regulation was achieved by overexpression of the gene for CK deactivating enzyme cytokinin oxidase/dehydrogenase (CKX): constitutive (35S:CKX) or at the stress onset using a dexamethasone-inducible pOp/LhGR promoter (DEX:CKX). The 35S:CKX plants exhibited slow ontogenesis and higher expression levels of stress-associated genes, e.g., AtP5CS1, already at well-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 54 publications
2
74
0
1
Order By: Relevance
“…However, recent studies have mainly focused on global transcriptomic, proteomic and metabolomic changes in various plant species with modulated cytokinin levels [105,122,250]. Thus, further detailed analysis is required to confirm the importance of identified candidate genes/proteins and validate their roles in stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have mainly focused on global transcriptomic, proteomic and metabolomic changes in various plant species with modulated cytokinin levels [105,122,250]. Thus, further detailed analysis is required to confirm the importance of identified candidate genes/proteins and validate their roles in stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Another important plant hormone that can have a positive role in the mitigation of drought stress is represented by the cytokinins. It has been demonstrated that Arabidopsis plants overexpressing genes involved in cytokinin biosynthesis showed higher drought stress tolerance [115]. These plant hormones have a preferential site of biosynthesis in roots, and drought stress seems to Reduced photosynthetic activity also affects sugar concentration since respiration under drought increases because the plant temperature increases [109].…”
Section: Mechanism Of Signal Transduction and Development Of Drought mentioning
confidence: 99%
“…CKX genes have also been shown to be involved in plant tolerance to abiotic stresses 12,[14][15][16] . Carabelli et al 17 demonstrated that AtCKX6 is critical for the growth arrest of the leaf primordium, which contributes to extension growth under shaded conditions.…”
Section: Introductionmentioning
confidence: 99%